(untitled) (Scientific journal of the Fergana State University, 2025)
Theoretical information about pragmalinguistics, a developing field of modern linguistics that covers today’s pressing issues, is presented. Examples given within the framework of Uzbek linguistics and English and German languages are also analyzed in detail. The specific features of speech act theory, isomorphic and allamorphic features of the "command" speech act in different systematic languages are considered. This article provides information about the field of pragmalinguistics, one of the important areas of modern linguistics. Pragmalinguistic factors such as social context factors, stylistic coherence and social status that make the "command" speech act possible in different systematic languages English, Uzbek and German are studied. Many factors underlying the field of the command speech act are considered through examples analyzed from fiction. At the same time, gender, age and many other components are thoroughly studied and concluded through examples.